The World Wars : an Introduction to the First & Second World Wars - Dowswell, Paul ; Brocklehurst, Ruth & Brook,Henry; Edited by Jane Chisholm (London Usborne, 2016)
The two world wars of 1914 -1918 and 1939 -1945 cast a malevolent shadow over the entire 20th Century. This book takes you through the story of both conflicts, from the soldiers' terrifying experiences of the trenches in the First War, to the huge battles and bombing of cities in the second. Stunningly illustrated with dramatic contemporary photographs, paintings, posters and maps, this is an accessible and thought-provoking introduction to the most devastating wars the world has ever known.
Include Coiour Illustration
Keywords: The World Wars -- Computer network resources -- World War, 1939-1945 -- Juvenile literature